„dovute grazie in musica“: Zwei neu entdeckte Briefe von Luigi Rossi - Heckendorff, Nastasia (Die Musikforschung, 2022)
This article presents and examines two newly discovered letters by the composer Luigi Rossi, (1597/1598–1653) as well as a letter written to him by the Duke Paolo Giordano Orsini II. Rossi represents one of the most famous musicians during the period of pope Urban VIII. Barberini and a key figure within the cultural exchanges between Rome and Paris. In 1647 his L’Orfeo, the first opera explicitly composed for France, was presented at the Palais Royal. The letters date from the later period in Rossi’s life (1645, 1648, and 1650) and are directed to aristocratic families: the Bentivoglio from Ferrara and the Savoy in Turin. Through analysis and contextualisation of the sources from diverse perspectives, the article throws new light on the composer’s biography regarding his activity as political informant and the cantata production during his second stay in France. The appendix of the article offers a critical edition of the letters.